1985
DOI: 10.1021/bi00343a035
|View full text |Cite
|
Sign up to set email alerts
|

Promotion and inhibition of vesicle fusion by polylysine

Abstract: Polylysine induced rapid aggregation of large unilamellar vesicles composed of phosphatidylcholine-cardiolipin (1:1 molar ratio) but not their fusion. Application of the terbium-dipicolinic acid fusion assay showed that addition of polylysine at nanomolar concentrations enabled a significant lowering of the Ca2+ threshold concentration for vesicle fusion from 9 to 1 mM. Analysis of the kinetics of fusion with a mass-action kinetic model showed that polylysine enhanced significantly the rate of aggregation but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

1988
1988
2006
2006

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 41 publications
3
23
0
Order By: Relevance
“…It is quickly endocytosed by a non-receptor-mediated pathway (Shen et al, 1985) and, because of this property, has been used as a carrier molecule for methotrexate into methotrexate-resistant cells (Shen & Ryser, 1979;Shen et al, 1985). The polymer induces membrane fusion in in vitro systems (Walter et al, 1986;Uster & Deamer, 1985;Gad et al, 1985), and selective membrane leakage has been observed at relatively high doses (Bashford et al, 1986). Stimulation of brain triglyceride lipase (Le Petit et al, 1986), as well as of a protein (casein) kinase (Leiderman et al, 1985) have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…It is quickly endocytosed by a non-receptor-mediated pathway (Shen et al, 1985) and, because of this property, has been used as a carrier molecule for methotrexate into methotrexate-resistant cells (Shen & Ryser, 1979;Shen et al, 1985). The polymer induces membrane fusion in in vitro systems (Walter et al, 1986;Uster & Deamer, 1985;Gad et al, 1985), and selective membrane leakage has been observed at relatively high doses (Bashford et al, 1986). Stimulation of brain triglyceride lipase (Le Petit et al, 1986), as well as of a protein (casein) kinase (Leiderman et al, 1985) have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Polylysine, which is known to promote liposomeliposome fusion [9][10][11], enhanced the binding of DNA-containing liposomes to protoplasts (Fig. 1), but apparently decreased the efficiency of expression of the introduced gene as measured by the CAT assay (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The maximum solubilization would be obtained at pH below I.E.P and at the swamping concentration of protein. It seems that the solubilizing properties of proteins should be noted as one of the important functions of macromolecules, as well as their physiological role in biological membranes [27][28][29].…”
Section: Discussionmentioning
confidence: 99%